Beliefs related to oral antidiabetic use among individuals with diabetes - Bernadete de Lourdes André Gouveia; Mailson Marques de Sousa; Taciana da Costa Farias Almeida; Vinicius André Gouveia de Sousa; Wilma Dias de Fontes Pereira; Simone Helena dos Santos Oliveira (Universidade Federal do Rio de Janeiro, 2019)
Abstract Objective: To identify beliefs related to oral antidiabetic use among individuals with type 2 diabetes mellitus, based on the Theory of Planned Behavior. Method: This is a descriptive, quantitative and qualitative study conducted with 32 participants using oral antidiabetic drugs. Data was collected through an open question tool and analyzed by number of emissions and content. Results: Among the behavioral beliefs, the following stand out: (a) as an advantage, to keep diabetes controlled; and (b) as disadvantages, gastric pain and discomfort, nausea and diarrhea. In the normative beliefs, family stood out as a social referent (children, mother and siblings). As for the control beliefs, taking the tablets with water and the size of the tablets stood out as practicalities and difficulties, respectively, in relation to the oral therapy follow-up. Conclusion and implications for practice: It was possible to identify the beliefs regarding the behavior of taking oral antidiabetics that will contribute to foster educational strategies with the potential to strengthen the positive beliefs and to revert the negative ones, in favor of adherence to drug therapy, glycemic control and quality of life.